A Study of the Adsorption Structures of Co Molecule on the MgO (001) Surface - Mahmoud A. Kawan; Moftah A. Ben Yazid; Ahmed A. Awhida (African Journal of Advanced Pure and Applied Sciences, 2025)
Using a Monte Carlo simulation model, the results showed that carbon monoxide (CO) molecules stabilize on the magnesium oxide surface (MgO) in either monolayer or multilayer structures. Each of these configurations has distinct thermal characteristics, which differentiate them in terms of unit cell configuration, number of molecules, tilt angles from the surface, vertical height, adsorption energies, and surface coverage ratios. The simulation results agreed significantly with previously obtained experimental results. At low temperatures, three configurations of type c(4×2) were identified, with each primitive cell containing six CO molecules. The molecules are predominantly adsorbed vertically over Mg⁺2 ions, with a 2:1 ratio of vertical to tilted molecules. The polar angle for tilted molecules was found to be 31°, consistent with Polarization Infrared Reflection Spectroscopy (PIRS) experimental values. Vertical molecules align directly above Mg2+ ions, while tilted ones are slightly displaced. The configurations alternate between vertical and tilted molecule rows. Monte Carlo simulations showed that this configuration remains thermally stable up to approximately 40 K. At this temperature, the p(3×2) configuration appears, accompanied by a decrease in coverage due to the replacement of tilted molecules with vertical ones. Only tilted molecules remain in the monolayer configuration at full coverage, while vertical molecules form in the multilayer arrangement.